A study on Pattern and outcome of Poisoning cases in Tertiary care Hospital in South India - Palimar, V; Gupta, C; Pratap, B (Journal of Indian Academy of Forensic Medicine, 2022)
Poisoning is the fourth common reason of mortality in India. Familiarity of common configuration of poisoning in a specific area will aid in prompt identification and management of cases, therefore reducing the frequency of death and morbidity. So, the aim of this study is study the pattern of all poisoning cases admitted to the hospital. 277 victims who were admitted in emergency triage due to poisoning in 1 year were included for the study. Data pertaining to age, sex, and toxic substance were analyzed. Age group was divided into 3 categories 15-40 yrs, 41-65 yrs and 66-90 yrs. Later the results were analyzed. Age group 15-40 years was more commonly involved. Males outnumbered females. Oral ingestion of poison was predominately seen. Most common poisoning was the organophosphorous insecticide poisoning which was seen in 24.18% of cases. Early care in a tertiary care center after identifying the poison may benefit in reducing death due to poisoning in India.